Local student perception towards foreign student in IIUM Gombak - Mohd Fadzil, Nur Hidayah; Md Sawari, Siti Salwa (2019)
Educational tourism become famous practices in worldwide as known as gaining knowledge while travelling somewhere. However, the cultural diversity happened in university campus can create positive and negative thoughts among local students because of different perception on multicultural environment. The aim of this study is to investigate the local students’ perception towards foreign students either it shows positive or negatively inclined .Thus the findings of this study will be reference for next research in order to observe on the potential of IIUM Gombak to be one of the International Educational Tourism university soon. Specifically, this research concentrate on quantitative research design using a none probability sampling method. The research findings represent collected data from questionnaire that has been distribute to local students of IIUM Gombak using online platform. The result obtained on local students’ perception towards foreign students from this study is based on 32 sample. Overall findings of this research shows local students had positive perception towards foreign students, however minor group of local student are not comfortable enough with the presence of foreign student because of their bad experiences in the past. The significant contribution of this study was to take ensure there are positive perception, interaction between local students towards foreign students to create successful and peaceful environment as potential education tourism university.